The Indirect Fiscal Benefits of Low-Skilled Immigration - Mark Colas; Dominik Sachs (Ludwig-Maximilians-Universität München und Humboldt-Universität zu Berlin, Collaborative Research Center Transregio 190 - Rationality and Competition, 2022)
Low-skilled immigrants indirectly affect public finances through their effect on resident wages & labor supply. We operationalize this indirect fiscal effect in a model of immigration and the labor market. We derive closed-form expressions for this effect in terms of estimable statistics. An empirical quantification for the U.S. reveals an indirect fiscal benefit for one average low-skilled immigrant of roughly 750 annually. The indirect fiscal benefit may outweigh the negative direct fiscal effect that has previously been documented. This challenges the perception of low-skilled immigration as a fiscal burden.
Keywords: H20; J31; J61; 330; immigration; fiscal impact; general equilibrium